Does gender equality promote social trust? An empirical analysis - Seo-Young Cho (Philipps-University Marburg, Faculty of Business Administration and Economics, 2015)
Fairness can be an important factor that promotes social trust among people. In this paper, I investigate empirically whether fairness between men and women increases social trust. Using the data of the World Value Survey from 91 countries, I find that gender discriminatory values negatively affect the trust level of both men and women, while actual conditions on gender equality, measured by labor and educational attainments and political participation, are not a significant determinant of social trust. Furthermore, fairness towards women is an important factor of social trust in countries where gender equality is relatively high, but the effect of the fairness is minimal in countries where there is a greater disparity in equality between the genders. Contrary to the expectation, the effect of gender equality is larger for men than women in more equal societies - a finding that calls for a closer look in a future study.
Keywords: I30; J15; J16; 330; trust; gender equality; fairness; value survey